Full-Thickness Scleral Rupture with Choroidal Prolapse, Grade III Hyphema, and Conjunctival Laceration Following Blunt Ocular Trauma: A Case Report - Angel Lim; Ni Kadek Puspa Mega Putri Sudibia (Eduvest - Journal of Universal Studies, 2026)
Open-globe injuries caused by blunt ocular trauma remain a major cause of irreversible monocular blindness worldwide. Full-thickness scleral rupture accompanied by choroidal prolapse and high-grade hyphema represents one of the most severe forms of ocular trauma, often resulting in poor visual outcomes despite prompt surgical intervention. Early recognition and immediate management are therefore essential to preserve globe integrity and minimize secondary complications. This study aims to describe the clinical presentation, emergency surgical management, and prognostic considerations of a patient with severe blunt ocular trauma presenting with full-thickness scleral rupture, grade III hyphema, and choroidal prolapse. A qualitative case report approach was employed. Clinical data were obtained from medical records, comprehensive ophthalmologic examinations, orbital computed tomography findings, intraoperative observations, and postoperative follow-up. The patient's clinical course was descriptively analyzed and interpreted according to current literature and established ocular trauma management guidelines. A 60-year-old male presented with no light perception following blunt trauma to the left eye after falling from stairs. Clinical examination revealed full-thickness scleral rupture, choroidal prolapse, grade III hyphema, conjunctival laceration, and canalicular injury. Emergency primary globe repair was successfully performed within six hours of injury, including scleral closure, conjunctival repair, repositioning of viable uveal tissue, and canalicular reconstruction. At one-week follow-up, the globe remained anatomically intact without evidence of endophthalmitis; however, visual acuity remained at no light perception, indicating an extremely poor functional prognosis. This case highlights that prompt surgical intervention is critical for preserving anatomical integrity and preventing postoperative complications in severe blunt open-globe injuries.